Health-related quality of life in Her2-positive early breast cancer woman using trastuzumab: A systematic review and meta-analysis - Khoirunnisa, Sudewi Mukaromah; Suryanegara, Fithria Dyah Ayu; Setiawan, Didik; Postma, Maarten Jacobus (Frontiers in Pharmacology, 2023)
Background Despite the benefits of trastuzumab in many trials, evidence of its impact on health-related quality of life (HRQoL) in early treatment has not been summarized. This study explored the effects of trastuzumab treatment on HRQoL, including pooled meta-analysis, in an effort to provide an integrated assessment of HRQoL for Her2-positive early breast cancer patients. Methods A comprehensive literature review to February 2023 using three databases, focusing on treatment using trastuzumab during the early stage, was performed. The mean changes from baseline during and after treatment were extracted from the included randomized control trials (RCTs) papers and total HRQoL scores were obtained from cross-sectional studies included. Mean difference (MD) and 95% confidence intervals were assessed by a random effect or fixed effect model based on heterogeneity (I2). Results A total of ten studies were identified and reviewed, consisting of seven RCTs and three cross-sectional studies. The pooled analysis of the mean change from baseline during treatment resulted in an MD of 1.92 (95% CI = 1.59 to 2.25, P < 0.05, I2 = 0%), favoring the trastuzumab group. A non-significant result of the mean change from baseline after treatment appeared in the analysis of 12-month follow-up. In the cross-sectional studies, pooled analyses of HRQoL showed that trastuzumab meaningfully demonstrated an improved HRQoL profile (MD = 9.29, 95% CI =1.31 to 17.27, P = 0.02, I2 = 0%). Conclusion Trastuzumab as a targeted therapy resulted in a favorable effect on HRQoL in the early stages of Her2-positive breast cancer. The findings of significant improvements in patients’ HRQoL and less clinically meaningful deterioration in side effects of trastuzumab-containing regimen during treatment were supported by prolonged survival.